Le Thť́re du soleil : the first fifty-five years - Picon-Vallin, Bǎtrice (Routledge, Taylor & Francis Group, 2021)
"Le Thť́re du Soleil traces the company's history from a group of young, barely trained actors, directors and designers struggling to match their political commitment to a creative strategy, to their grappling with the concerns of migration, separation and exile in the early decades of the 21st century. Bǎtrice Picon-Vallin recounts how, in the fifty-five years since their founding, Thť́re du Soleil have established themselves as one of the foremost names in modern theatre. Ariane Mnouchkine and her collaborators have developed a unique and ever-evolving style that combines a piercing richness of shape, colour, and texture with precision choreography, innovative musical accompaniment, and multi-layered, metaphorical dreamscapes. This rich, storied history is illustrated by a wealth of spectacular rehearsal and production photos from the company's own archive and interviews with dozens of past and present members, including Mnouchkine herself. Judith G. Miller's timely translation of the first comprehensive history and analysis of a remarkable, award-winning company is a compelling read for both students and teachers of Drama and Theatre Studies"--